Supreme ambition [compact disc, unabridged] : Brett Kavanaugh and the conservative takeover - Marcus, Ruth (Simon & Schuster Audio, 2019)
The Republicans began plotting their takeover of the Supreme Court thirty years ago. Brett Kavanaugh set his sights on the court right out of law school. Washington Post journalist and legal expert Ruth Marcus goes behind the scenes to document the inside story of how their supreme ambition triumphed.